Burnout rates among Lebanese pre-final and final year medical students during the COVID-19 pandemic: A multi-centered survey-based study. - Nasr, Cassandra; Bou Sanayeh, Elie; Nasr, Cynthia; Merheb, Georges; Massoud, Marcel (Work, 2023)
BACKGROUND: Burnout among medical students has always been a major concern. OBJECTIVE: To evaluate changes in the prevalence rates of burnout among Lebanese pre-final and final year medical students while taking into consideration the impact of coronavirus 2019 (COVID-19) on both the academical and clinical experiences. METHODS: This is a multi-centered, survey-based, cross-sectional study conducted in October 2021. The Copenhagen Burnout Inventory questionnaire was used on 120 medical students from three different medical schools in Lebanon. RESULTS: The overall burnout prevalence was 40.01%. When further dividing it into domains, 39.36% of students had personal burnout, 41.52% had work-related burnout, and 39.16% had pandemic-related burnout. Theoretical learning and clinical training were reported to be affected in respectively 66.70% and 71.70%. However, only 10.00% of the students have regretted choosing medicine and 67.50% felt comfortable to get to the next academic level. CONCLUSION: High levels of burnout were reported among pre-final and final year medical students with a subsequent negative impact on their academic life and clinical training. Medical schools should start adopting a conscious view of how to guide medical students in finding adequate coping mechanisms during these times of crisis.